DEVELOPING STUDENTS’ ORGANIZATIONAL COMPETENCIES IN THE CONTEXT OF MODERN EDUCATION - Marguba Mirqosimova (Western European Studies, 2025)
This article examines the relevance of developing students’ organizational competencies as a key factor in improving the quality of education and preparing professionally competent personnel who meet contemporary social demands. The study substantiates that the formation of organizational qualities contributes to the development of leadership potential, initiative, responsibility, and effective teamwork skills among students. Particular attention is paid to competency-based and innovative approaches in modern education, which ensure the integration of theoretical knowledge with practical activities. The article highlights effective mechanisms for developing organizational qualities through both curricular and extracurricular activities, including problem-based learning, group work, creative assignments, school cultural events, celebrations, and intellectual competitions such as “Fun and Clever” contests. These activities foster students’ communication skills, decisionmaking abilities, collective responsibility, and moral-ethical values. The role of extracurricular clubs in organizing students’ leisure time productively and enhancing their independence, discipline, and collaborative skills is also emphasized.
Keywords: Modern Education; Educational Effectiveness; Organizational Competencies